1985
DOI: 10.1172/jci112113
|View full text |Cite
|
Sign up to set email alerts
|

Nasal challenge with cold, dry air results in release of inflammatory mediators. Possible mast cell involvement.

Abstract: The purpose of our study was to assess the effect of cold, dry air (CDA) on the nasal mucosa of selected individuals in relation to the release of inflammatory mediators associated with mast cells. 12 subjects with a history of nasal symptoms of rhinorrhea and congestion upon cold or dry environmental exposure were challenged by nasal breathing of CDA and warm, moist air (WMA). Each subject was tested on two occasions with the order of the challenges reversed. Symptom scores were recorded, and the levels of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
133
2
3

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(141 citation statements)
references
References 39 publications
(32 reference statements)
3
133
2
3
Order By: Relevance
“…Previous studies have assessed the role of CPAP on nasal airway of healthy volunteers [8][9][10]16] and in a rodent model [11], and have also evaluated the effect of different forms of humidification on nasal symptoms and adherence in OSA patients [13][14][15]22]. However, the effect of CPAP (with and without humidification) on nasal airway pathophysiology of OSA patients remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have assessed the role of CPAP on nasal airway of healthy volunteers [8][9][10]16] and in a rodent model [11], and have also evaluated the effect of different forms of humidification on nasal symptoms and adherence in OSA patients [13][14][15]22]. However, the effect of CPAP (with and without humidification) on nasal airway pathophysiology of OSA patients remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiologic mechanisms by which CPAP causes cytokine release are unknown, some speculations can be made. It is likely that airflow of cold and dry air has a toxic effect on nasal epithelium [26] and mediator containing cells of the nasal mucosa [10]. The addition of heated humidification could eventually prevent this effect, thus avoiding epithelial detachment and shedding and mediator release.…”
Section: Sleep-related Disorders I Koutsourelakis Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the methodological problems encountered when sampling plasma histamine [18] and its short half-life in the circulation, approximately 1 min [19], it has been suggested that elevations in plasma histamine mainly reflect the basophilia which normally accompanies exercise [20]. Increases in the levels of tryptase and PGD 2 , both specific mast cell markers, have been detected in nasal lavage following nasal provocation with cold dry air [21], but not after exercise [22,23].…”
Section: Aamentioning
confidence: 99%